Evaluation of exhaust gas recirculation techniques on a high-speed direct injection diesel engine using first law analysis. (February 2019) - Papaioannou, Nick; Leach, Felix CP; Davy, Martin H; Weall, Adam; Cooper, Brian
The effects of different exhaust gas recirculation (EGR) strategies on engine efficiency and the resulting energy flows at two speed/load conditions (1500 r/min/6.8 bar net indicated mean effective pressure (nIMEP) and 1750 r/min/13.5 bar nIMEP) were studied using a first law analysis approach. The EGR strategies tested were as follows: cooled high-pressure exhaust gas recirculation (baseline), the application of exhaust gas recirculation with the swirl flap closed and the use of exhaust gas recirculation under constant λ conditions. The closed swirl flap exhaust gas recirculation strategy reduced brake efficiency under high load conditions and increased heat transfer to the coolant for both load cases. Soot and CO emissions increased at high load, however, with an increase in NOx relative to the baseline case. The constant λ exhaust gas recirculation strategy reduced brake efficiency under low load, as well as the heat flow to the coolant for both load cases. The constant λ exhaust gas recirculation strategy benefited smoke emissions and increased combustion exhaust gas recirculation tolerance, albeit with a penalty in NOx emission.